Pengaruh Biaya Lingkungan Dan Kinerja Lingkungan Terhadap Kinerja Keuangan - Elyanti Rosmanidar; Marissa Putriana; Melvy Aulia Putri Nasution (STEKOM PRESS, 2024)
The basic materials sector company is one of the sectors that is expected to have bright prospects in the future and is one of the sectors that has a sizable role in contributing raw materials. If we look at the stock prices of several basic materials companies, they have experienced erratic increases and decreases. The high and low stock prices are influenced by how the company's financial performance is. The data used in this research is secondary data, namely in the form of annual reports of companies in the basic materials sector for 2017-2021. This research is descriptive with a quantitative approach. The statistical method used is simple regression analysis, panel data regression method, F test, t test, and analysis of the coefficient of determination. The results showed that environmental costs had a partial positive and significant effect on the financial performance of basic materials sector companies listed on the Indonesian Sharia Stock Index. Environmental performance had a partial positive and significant effect on financial performance in basic materials sector companies listed on the Sharia Stock Index. Indonesia. Then environmental costs and environmental performance have a positive and significant simultaneous effect on financial performance in basic materials sector companies listed on the Indonesian Sharia Stock Index.